The Professional Competency Development Model of Science Teachers through Learning Leadership - Utaminingsih, S.; Sundari, S.; Mirana, A. E. (Jurnal Pendidikan IPA Indonesia, 2024)
This research aims to analyze the model for developing the professional competence of science teachers through learning leadership. This method is quantitative research applied to a survey with a cross-sectional design. The participants were the science teachers at Pati residency, with 240 respondents. The researchers collected a questionnaire consisting of 46 validated questions with estimated reliability. The questions consisted of four teacher competence models and three leadership learning indicators. The researchers analyzed with the Structural Equation Modeling, SEM. Based on the data analysis, the science teacher competency development model is positively influenced by learning leadership by 15% in the small category. It also showed that the science teacher competency model formed from indicators of professional development and learning practices is in the large category, while professional knowledge and soft skills are in the moderate category. This research concluded that learning leadership contributed little to the science teacher competency development model. In the era of independent learning, it was important for school principals to increase the development of professional competency models for science teachers so that they can implement student-centered learning. The results of these findings provided input to school principals to improve their leadership in managing teacher learning, starting from planning, learning processes, evaluation, and reflection, while science teachers to improve their professional competence through learning activities with lesson studies and research actions as well as activities outside of learning such as training and seminars.